Preparation and Characterization of Chitosan-Gelatin Film for Wound Dressing - Mutiara, Mutiara; Purwangnityas, Fiska Yohana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to explore the effect of various components of chitosan gelatin on its characteristics. The method used was drying at room temperature using petridish for 2-3 days, by mixing all raw materials with chitosan : gelatin weight ratio of 1:0, 0:1, 1:1, 1:2, and 2:1. The dried film was taken and tested for film characteristics. The analysis conducted was FTIR analysis, swelling analysis, and degradation analysis. The results of the swelling analysis showed that the more the addition of gelatin composition, the percentage of swelling increased as shown in the ratio of 1:2, namely 85.178%, 144.072%, 102.068%, 184.660%, 135.272%. Meanwhile, the degradation test results showed that the chitosan and gelatin films with various composition variations increased as the test time progressed. FTIR analysis revealed that gelatin (Ge), chitosan (Ch), and chitosan-gelatin mixture (Ch-Ge) with 1:1 ratio had similar absorption peaks.